Temporarily Aligned Interest: Cooperation Between Turkey and The United States in The Syrian Civil War – A Foreign Policy Perspective - Muhammad Arkan; Rodon Pedrason; Syaiful Anwar (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
The Syrian Civil War, starting from 2011 and still ongoing, is one of the largest conflicts in the region which highly affected the overall stability of the region and has involved several parties. The United States along with Turkey sided with anti-government rebellions and actively supported them by supplying weapons and munitions, along with military training. However, despite having mutual interest on supporting rebels and later countering ISIS offensives, the Interests of Turkey and US are not always in-line with each other. Using the perspective of realism theory of international relations, this research attempts to highlight a case where cooperations between countries tend to prioritise the benefit of their own countries over their partners. Academically, this paper also contributes on adding an analysis based off realist perspective in relation to the Syrian conflict